Plasma glutamine levels and falciparum malaria. - Cowan, G; Planche, T; Agbenyega, T; Bedu-Addo, G; Owusu-Ofori, A; Adebe-Appiah, J; Agranoff, D; Woodrow, C; Castell, L; Elford, B; Krishna, S (1999)
Glutamine deficiency is associated with increased rates of sepsis and mortality, which can be prevented by glutamine supplementation. Changes in glutamine concentration were examined in Ghanaian children with acute falciparum malaria and control cases. The mean (SD) plasma glutamine concentration was lower in patients with acute malaria (401 (82) mumol/L, n = 50) than in control patients (623 (67) mumol/L, n = 7; P < 0.001). Plasma glutamine concentrations all rose in convalescence. The mean (SD) increase in plasma glutamine was 202 (123) mumol/L (n = 18; P < 0.001) compared with acute infection. We conclude that acute falciparum malaria is associated with large decreases in plasma glutamine and these falls may increase susceptibility to sepsis and dyserythropoeisis.